Fundamental Consideration of Truth – in general and in Criminal Law - Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
In this paper the author deals with the eternal issue of truth - in general and in criminal law. In the first part of the paper the author speaks about the significance of truth as such, but also about its role and place in contemporary society. He continues elaborating the idea of truth as it was in ancient Greek philosophy and poetic tradition given that Ancient Greece represents the cradle of the idea of truth. This part of the paper ends with an analysis of the Aristotle’s understanding of truth which is, according to the author, the beginning of the new era of modern understanding of the truth phenomenon. In the following part of his paper the author analyses the opinions of the 20th century outstanding philosophers who occupied themselves with so called factual truth – which, in his opinion, includes the truth reached in criminal law. This type of truth is analysed further. The author concludes that the maximum to be reached in the criminal procedure is conviction i.e. belief that we are in the possession of truth. When reaching „objective“ truth is concerned as undoubtless certainty that a criminal offence has been commited, as well as all details referring to its commission, the author believes that this is the “eternal” but never accomplished ideal. Finally, the author proposes the modality of truth, which is most likely to be accomplished within criminal law and procedure.